Water Quality Assessment and Monitoring of Closed Rearing System of the Sea Cucumber Holothuria scabra - Hanny Meirinawati; Hanif Budi Prayitno; Lisa Fajar Indriana; Muhammad Firdaus; A'an Johan Wahyudi (ASEAN Journal on Science and Technology for Development, 2020)
Sea cucumbers are an essential fishery resource. Therefore, effective aquaculture methods should be developed to achieve their optimal production. Sea cucumbers are susceptible to various environmental factors, one of which is water quality. Monitoring water quality based on physical and chemical parameters should be useful to the rearing system in aquaculture. In practical use, farmers usually monitor only temperature, salinity, and pH, neglecting the essential role of chemical parameters. This review focuses on and urges the monitoring of physical and chemical parameters. We explored the water quality parameters that may be crucial to the sea cucumber rearing system, including temperature, salinity, pH, dissolved oxygen, ammonia, turbidity, particulate organic matter, total nitrogen, nitrate, nitrite, ammonium, silicate, and phosphate. Furthermore, this paper presents a practical way to monitor the aquaculture or rearing system of sea cucumbers. It is suggested that temperature and salinity are the crucial physical parameters, while the essential chemical parameters are phosphate, nitrate, and ammonia.